Childhood case histories that may have misled you - Senanayake, M.P. (My University, 2008)
It is standard medical student teaching that history taking forms the foundation on which the diagnostic process stands. The different components of the history are vital for pronouncing prognosis too. In addition, in the field of paediatrics, the social history and birth history are of predictive value for the final outcome of childhood itself. It is however important that paediatricians, adept as they may be at eliciting history, are never prophetic. It is in this light that these histories are reproduced for your consideration.